MENINGKATKAN HASIL BELAJAR BOLA BASKET MELALUI PERMAINAN RANGKAIAN 3 POS PADA SISWA KELAS V SD NEGERI 14 MULYOHARJO KECAMATAN PEMALANG KABUPATEN PEMALANG TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aims to improve the quality of physical education learning materials mainly through approachesplaying basketball. The research was conducted in the learning process, research is often called action research(classroom Action Research), an act in this study were divided into three cycles and implemented in threemeetings, in each cycle shows the learning process of physical development with basketball material. Thesubjects were fifth grade students of SD Negeri 14 mulyoharjo in the second semester of academic year2012/2013. The instrument used for data collection in this study was the observation sheets, questionnaires,and student test performance. Analysis of the data used in this study is a descriptive analysis.The resultsshowed that the implementation of learning to play basketball with the approach can make their lessons moreactive, enthusiastic students participating in learning and seemed happy to perform a given task motion so thatthe teacher and the student movement skill mastery basketball increase of the percentage of students who precyclevalue KKM achieve as much as 63.16% or 12 children out of the total number of students by 19 students,the first cycle measures the percentage of students that reached KKM be 73.68% or as many as 14 students and89.47% or as many as 17 students in the second cycle of action .